1998
DOI: 10.1111/j.1572-0241.1998.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Prospective Trial of Early Versus Delayed Feeding After Percutaneous Endoscopic Gastrostomy Placement

Abstract: Early initiation of PEG feedings is safe, well tolerated, and reduces cost by decreasing hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(18 citation statements)
references
References 10 publications
0
15
0
3
Order By: Relevance
“…It was expected that, during that time, the GI system returns to normal function and better seal of the enteral opening is achieved (138 -140). Later, several prospective randomized studies (141)(142)(143)(144)(145) clearly demonstrated that earlier initiation of feeding at 3 hours (141,142), 4 hours (143), and even immediately (144) is safe. These data were further analyzed and confirmed in metaanalysis by Bechtold et al (145) that summarized six randomized trials.…”
Section: Initiation Of Feedingmentioning
confidence: 99%
“…It was expected that, during that time, the GI system returns to normal function and better seal of the enteral opening is achieved (138 -140). Later, several prospective randomized studies (141)(142)(143)(144)(145) clearly demonstrated that earlier initiation of feeding at 3 hours (141,142), 4 hours (143), and even immediately (144) is safe. These data were further analyzed and confirmed in metaanalysis by Bechtold et al (145) that summarized six randomized trials.…”
Section: Initiation Of Feedingmentioning
confidence: 99%
“…L'utilisation pr6coce de la sonde clans les 3 ~ 6 heures peut se faire sans risque, en perfusant en premier lieu du sdrum sal6 st6rile pour ddtecter une fuite p6ri-ton6ale [20,21].…”
Section: Apr~s La Poseunclassified
“…The first choice for surgical patients who will not be submitted to laparotomy is percutaneous endoscopic gastrostomy (PEG). This fast, easy procedure can be done with local anesthesia at the bedside; it has low morbidity rates and permits early initiation of enteral feeding [28]. Relative contraindications include previous upper abdominal surgery, obesity, and bleeding disorders.…”
Section: Gastrostomymentioning
confidence: 99%